Comparative Study of Surface Finish and Dimensional Accuracy in FDM 3D Printed Parts (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Fused Deposition Modeling (FDM) has emerged as one of the most widely adopted additive manufacturing technologies due to its cost-effectiveness, design flexibility, and ease of operation. However, the quality of FDM-fabricated components is often limited by issues related to surface finish and dimensional accuracy, which are critical parameters for functional and end-use applications. This paper presents a comparative study on the influence of key FDM process parameters on surface roughness and dimensional deviation of 3D printed parts. Standard test specimens were fabricated using commonly used thermoplastic materials under varying printing conditions, including layer thickness, print speed, build orientation, and infill density. Surface finish was evaluated using surface roughness measurements, while dimensional accuracy was assessed through precise dimensional inspection and deviation analysis. The experimental results reveal that layer thickness and build orientation have a significant impact on surface quality, whereas print speed and infill density play a crucial role in dimensional stability. A comparative analysis is carried out to identify optimal parameter combinations that achieve improved surface finish without compromising dimensional accuracy.